ANALISIS ASAS SEDERHANA, CEPAT DAN BIAYA RINGAN DALAM HUKUM ACARA PERDATA: STUDI KASUS PENGAJUAN REKONVENSI - Lubis, Fauziah; Harahap, Aisyah; Sains, Ihsan Hidayah; Aulia, Nuha; Pulungan, Ro’fat Ja’far Al-hadidi; Syarzain, Yuyun Sari (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This observe examines the software of the standards of simplicity, velocity, and occasional price within Indonesian civil procedural regulation, especially concerning the submitting of reconvention as a counter-claim. those ideas are critical for the management of justice, as mandated with the aid of Article 2 paragraph (four) of law No. forty eight of 2009 on Judicial strength. Reconvention, which is a counter-declare made through the defendant against the plaintiff inside the same case, holds massive potential for embodying these three ideas. The studies employs a literature assessment method, studying numerous prison texts, policies, and case research of reconvention practices across extraordinary courts. Findings suggest that reconvention methods, when filed alongside the defendant's reaction and addressed in a single series of hearings, can exemplify the precept of simplicity by means of keeping off complex processes, the principle of speed by way of shortening trial periods, and the precept of low value through preventing the duplication of prices.Case studies conducted at the Sidrap Religious Court and in land dispute cases demonstrate the effectiveness of reconvention in enhancing judicial efficiency. The study concludes that reconvention serves as an effective procedural law tool for achieving the principles of simplicity, speed, and low cost, while also emphasizing the need to uphold the principles of justice and legal certainty in its implementation.